Exodus - Gispen, Willem Hendrik, 1900- (Grand Rapids, MI Zondervan, 1982)
Includes bibliographical references.
originally published under the title " Korte Verklaring der Heilige Schrift", The Netherlands, J.H. Kok andB.V. Kampen.
Keywords: Bible. O.T. Exodus -- commentaries